Synthesis and Activity Test of Cu/ZnO/Al2O3 for the Methanol Steam Reforming as a Fuel Cellâs Hydrogen Supplier - Makertihartha, IGBN; Subagjo, Subagjo; Gunawan, Melia Laniwati (Journal of Engineering and Technological Sciences, 2009)
The synthesis of hydrogen from hydrocarbons through the steam reforming of methanol on Cu/ZnO/Al2O3 catalyst has been investigated. This process is assigned to be one of the promising alternatives for fuel cell hydrogen process source. Hydrogen synthesis from methanol can be carried out by means of methanol steam reforming which is a gas phase catalytic reaction between methanol and water. In this research, the Cu/ZnO/Al2O3 catalyst prepared by the dry impregnation was used. The specific surface area of catalyst was 194.69 m2/gram.The methanol steam reforming (SRM) reaction was carried out by means of the injection of gas mixture containing methanol and water with 1:1.2 mol ratio and 20-90 mL/minute feed flow rate to a fixed bed reactor loaded by 1 g of catalyst. The reaction temperature was 200-300 °C, and the reactor pressure was 1 atm. Preceding the reaction, catalyst was reduced in the H2/N2 mixture at 160 °C. This study shows that at 300 °C reaction temperature, methanol conversion reached 100% at 28 mL/minute gas flow rate. This conversion decreased significantly with the increase of gas flow rate. Meanwhile, the catalyst prepared for SRM was stable in 36 hours of operation at 260 °C. The catalyst exhibited a good stability although the reaction condition was shifted to a higher gas flow rate.